Using an Evaluation Grid to Holistically Assess Library Databases. Issue 1 (8th February 2022) - Durrant, Summer
Abstract: When evaluating subscription-based databases, academic librarians primarily rely on cost-per-use statistics to guide their decision-making. Although this metric is useful, it does not provide a complete picture of a resource's value to the institution. To adopt a more holistic approach, the University of Mary Washington implemented an evaluation grid, which was used to assess 61 products the library subscribed to during the 2019–2020 academic year. In addition to product cancelations, results were used to identify areas for improvement. Using an evaluation grid enabled UMW Libraries to make high-quality renewal and cancelation decisions in an objective and transparent manner and effectively communicate these decisions to various stakeholders. Libraries wishing to holistically assess their databases can adapt the evaluation grid to meet their local needs.